PENGARUH TANGGUNG JAWAB, PENGALAMAN, INDENPEDENSI DAN INTEGRITAS TERHADAP PRESTASI KERJA AUDITOR DI KANTOR AKUNTAN PUBLIK MEDAN - Munthe, Ernes Sariah S; Putri, Chantika Tri; Khofifah, Diah; Pratama, Ayang; Lubis, Yeti Meliany (Journal Accounting International Mount Hope, 2025)
The study investigates the role of public accountants (KAP) in enhancing the reliability of financial reports, underscoring their responsibility and independence. The research highlights how professional performance correlates positively with experience, citing past studies supporting this claim. It integrates personality variables, particularly responsibility, as a critical component influencing auditor performance, based on the Acsription Responsibility Questionnaire (ARQ). The study replicates Kalbers and Cenker's research, suggesting responsibility significantly impacts auditors' effectiveness. It proposes that understanding these factors improves client satisfaction and credibility, establishing a foundation for future studies in the Indonesian context